Self-Reported Skin Sensation by People Who Have Experienced Containment During COVID-19 Pandemic - Kluger N; Le Floc'h C; Niore M; Delvigne V; Le Dantec G; Taieb C (Dove Medical Press, 2020)
Nicolas Kluger, 1 Caroline Le Floc’h, 2 Margot Niore, 2 Veronique Delvigne, 2 Guénaële Le Dantec, 2 Charles Taieb 3 1Dermatology, Venereology, Allergology, Skin and Allergies Hospital, University of Helsinki and Helsinki University Central Hospital, Helsinki, Finland; 2Direction Scientifique, Laboratoire La Roche Posay, Levallois Perret, France; 3Patients Priority Department, European Market Maintenance Assessment [EMMA], Fontenay Sous Bois, FranceCorrespondence: Charles TaiebEuropean Market Maintenance Assessment [EMMA], 18 Rue de la Renardière, 94120, Fontenay Sous Bois, FranceEmail charles.taieb@emma.clinicEfforts to curb the spread of the new coronavirus (SARS-CoV-2) have led to an unprecedented simultaneous containment of almost two-thirds of the world’s population. The excessive use of hand washing and hand disinfection has been associated with an increased incidence of irritant and allergic contact eczema in health care workers.1 Face masks and headgear worn tightly for prolonged hours are also responsible for various cutaneous conditions, such as contact allergies, irritation, friction dermatitis, abrasions and aggravation of chronic dermatoses.2 Some authors also suspect that chilblains (“COVID toes”), which were  widely reported in spring 2020, could be related to the containment rather than to direct SARS-CoV-2 infection.3 In addition, sensitive skin is a frequent condition in Western countries, ranging from 26 to 57% of the population, depending on the country.4 Sensitive skin is defined by the occurrence of unpleasant sensations in response to stimuli that should not normally provoke such sensations. The causative factors of skin sensitivity include physical (heat, cold, wind, or ultraviolet radiation), chemical (cleansers, cosmetics, water, or pollutants), psychological (emotional change or stress), or hormonal (menstrual cycle) factors.4,5